2021
DOI: 10.1007/s00787-021-01799-2
|View full text |Cite
|
Sign up to set email alerts
|

Altered gut microbiota correlates with cognitive impairment in Chinese children with Down’s syndrome

Abstract: Down's syndrome (DS), a common chromosomal disease caused by chromosome 21 trisomy, is the main cause of cognitive impairment in children worldwide. Emerging evidence suggests that the microbiota–gut–brain axis plays a potential role in cognitive impairment. However, data regarding gut microbiota alterations in DS patients remain scarce, especially data from children with DS. This case–control study was conducted to explore the gut microbiota composition in Chinese DS children. Additionally, the potential asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 44 publications
4
11
0
1
Order By: Relevance
“…As a comparison of the group differences at the Blautia genus level, the quantitative PCR results showed that the relative abundance (RA) of Blautia was significantly decreased in the intestinal tract of children with DS (P < 0.05, Figure 2A). This result was consistent with our previous findings (Ren et al, 2022), which showed a significantly lower level of Blautia in children with DS. Taken together, these results indicate that the Blautia genus is disturbed in individuals with DS.…”
Section: Differences In the Relative Abundance Of Blautia Species Bet...supporting
confidence: 94%
See 4 more Smart Citations
“…As a comparison of the group differences at the Blautia genus level, the quantitative PCR results showed that the relative abundance (RA) of Blautia was significantly decreased in the intestinal tract of children with DS (P < 0.05, Figure 2A). This result was consistent with our previous findings (Ren et al, 2022), which showed a significantly lower level of Blautia in children with DS. Taken together, these results indicate that the Blautia genus is disturbed in individuals with DS.…”
Section: Differences In the Relative Abundance Of Blautia Species Bet...supporting
confidence: 94%
“…Cognitive tests were conducted by two well-trained pediatricians in a hospital conference room with no interference. As described in our previous study (Ren et al, 2022), the scores of FSIQ, PRI, VCI, WMI and PSI were all decreased in the DS group (all P < 0.001). The correlation coefficient of this type is approximately 0.857.…”
Section: Assessments Of Cognitive Functionsupporting
confidence: 83%
See 3 more Smart Citations